2020
DOI: 10.1002/anie.202011358
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Metal Single‐Phosphorus‐Atom Catalysis of Hydrogen Evolution

Abstract: Non‐metal‐based single‐atom catalysts (SACs) offer low cost, simple synthesis methods, and effective regulation for substrates. Herein, we developed a simplified pressurized gas‐assisted process, and report the first non‐metal single‐atom phosphorus with atomic‐level dispersion on unique single‐crystal Mo2C hexagonal nanosheet arrays with a (001) plane supported by carbon sheet (SAP‐Mo2C‐CS). The SAP‐Mo2C‐CS is structurally stable and shows exceptional electrocatalytic activity for the hydrogen evolution react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 77 publications
(10 reference statements)
3
41
0
Order By: Relevance
“…So far, there have been limited studies on single‐atom iodine and single‐atom phosphorus electrocatalysts for alkaline HER. [ 116,117 ] The concept of non‐metal SACs has also been found to be of potential interest in CO 2 RR to multi‐electron reduction products.…”
Section: Designing Sacs For Multi‐electron Reduction Of Co2mentioning
confidence: 99%
“…So far, there have been limited studies on single‐atom iodine and single‐atom phosphorus electrocatalysts for alkaline HER. [ 116,117 ] The concept of non‐metal SACs has also been found to be of potential interest in CO 2 RR to multi‐electron reduction products.…”
Section: Designing Sacs For Multi‐electron Reduction Of Co2mentioning
confidence: 99%
“…[1] A promising strategy to solve this problem is the electrocatalytic water splitting for high-purity hydrogen generation to store the electric energy in the chemical bond of molecular hydrogen. [2] The molecular hydrogen with only water as the combustion product composes an important part of the renewable energy landscape in the future. [3] Alkaline water electrolyzer is a traditional and mature technique for electrocatalytic hydrogen evolution reaction (HER).…”
mentioning
confidence: 99%
“…Specifically, N, S and P non-metal heteroatoms have been introduced into Mo 2 C to tune its high-density empty d-orbits, resulting in a suitable hydrogen adsorption energy to alleviate hydrogen atom desorption propitious to boost HER activity. 1,19–22 Moreover, delicate doping of metal heteroatoms (Fe, 13 Co 5 and Ni 14 ) with a small amount into Mo 2 C also can effectively promote the hydrogen adsorption and evolution. Specifically, the modulation of electronegativity, closely related with rich electrons from metal heteroatoms mentioned above, will bring Mo 2 C a favorable Mo–H adsorption energy by offering partial electrons from metal heteroatom to Mo atom in order to lower the unoccupied d-orbitals of Mo.…”
Section: Introductionmentioning
confidence: 99%
“…20 On the other hand, P doped Mo 2 C and Ni, P co-doped Mo 2 C also possess excellent HER activity. 21,22 Thus, beneficial electron interaction could be expected in Mn, P co-doped Mo 2 C. However, few studies on Mn, P co doped Mo 2 C have been reported.…”
Section: Introductionmentioning
confidence: 99%